2014
DOI: 10.1007/s00464-013-3385-6
|View full text |Cite
|
Sign up to set email alerts
|

Robotic gastrectomy versus laparoscopic gastrectomy for gastric cancer: comparison of surgical performance and short-term outcomes

Abstract: Comparing well with laparoscopic gastrectomy, robot-assisted gastrectomy is a feasible and safe surgical procedure with clear operation field, precise dissection, minimal trauma, and fast recovery. Longer follow-up time and randomized, clinical trials are needed to evaluate the clinical benefits and long-term oncological outcomes of this new technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
83
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(95 citation statements)
references
References 28 publications
9
83
2
1
Order By: Relevance
“…The author hypothesized that this was due to the surgeon's competence in laparoscopy and to some limits in robotic surgery, including the absence of tactile feedback and lack of various robotic instruments such as a suction-irrigator and endo-staplers. On the other hand, a number of retrospective studies [12,13] reported a significantly lower estimated blood loss during RAG than during laparoscopic and open surgery, as confirmed in several meta-analyses [1,15,21,28,30]. The use of robotics seems to reduce blood loss even in major and complex surgical procedures, because it allows for an extremely accurate and clean dissection especially during difficult procedures such as extended lymphadenectomies.…”
Section: Perioperative Outcomesmentioning
confidence: 95%
“…The author hypothesized that this was due to the surgeon's competence in laparoscopy and to some limits in robotic surgery, including the absence of tactile feedback and lack of various robotic instruments such as a suction-irrigator and endo-staplers. On the other hand, a number of retrospective studies [12,13] reported a significantly lower estimated blood loss during RAG than during laparoscopic and open surgery, as confirmed in several meta-analyses [1,15,21,28,30]. The use of robotics seems to reduce blood loss even in major and complex surgical procedures, because it allows for an extremely accurate and clean dissection especially during difficult procedures such as extended lymphadenectomies.…”
Section: Perioperative Outcomesmentioning
confidence: 95%
“…On the contrary, robotic surgery shows comparable or better retrieval of lymph nodes than laparoscopy (16,17,19,21,23,25). The reduced number of retrieved lymph nodes is the one single weakness of laparoscopic surgery, compared with open surgery, for which robotic systems can compensate.…”
Section: Higher Number Of Retrieved Lymph Nodesmentioning
confidence: 99%
“…In robotic gastrectomy, about half of all publications report less bleeding than that in laparoscopic surgery (7,17,20,(23)(24)(25)(26)(27)(28). Statistically, less bleeding may have no impact on the clinical course of the patients; however, it implies that robots offer more precise dissection of the lymph nodes following the surgical plane.…”
Section: Less Bleedingmentioning
confidence: 99%
“…As for tumor recurrence, it was 4.2% in the robotic and 7.1% in the laparoscopic group during a follow‐up period of 15 and 19 months, respectively 24. As for long‐term survival and recurrence, although some studies have shown it was similar for both laparoscopic and robotic surgery, longer follow‐up periods with larger sample size studies that include advanced gastric cancer patients are still required to determine the oncological efficacy of robotic surgery.…”
Section: Oncological Outcomesmentioning
confidence: 99%